Hamiltonian Mechanics of Gauge Systems. - Prokhorov, Lev V. (Cambridge monographs on mathematical physics., 2011)
An introduction to Hamiltonian mechanics of systems with gauge symmetry for graduate students and researchers in theoretical and mathematical physics.